CONFLICT OF IRISH CULTURAL IDENTITY IN BRIAN FRIEL’S TRANSLATION - Andayani, Ambar; Basuki, Edi Pujo; Mustofa, Ali (Magistra Andalusia: Jurnal Ilmu Sastra, 2022)
Having been colonized by Britain, Ireland was in a very deprived condition for a very long period, especially for poor Catholic Irish. Britain had destroyed Irish civil rights by forcing them in a massive potato plantation merely to fulfill British people’s need for food, which caused the Irish in a great famine and poverty. Written by an Irish playwright in 1980, which is set in agricultural land, northern side of Ireland, Brian Friel’s Translations illustrates clearly the suffering of Irish villagers in 19th century. By applying Homi K. Bhabha’s post-colonialism theory, the dialogues from the play are analyzed to explain Irish cultural identity conflict. This play is analyzed by using a descriptive qualitative method. The result of analysis reflects the mimicry concept from Bhabha, in which it shows an ambition that Irish tradition must be vanished and replaced by British tradition. The dialogues in Brian Friel’s Translation describe that Irish language and tradition which tells a lot of Greek mythology must be replaced with the culture of Standard English language. The translations on Irish local place names into English language are forced for the sake of British imperialism importance in the Ordnance survey.